Co-existence of KMT2A::SEPTIN6 fusion and DIS3 variant in a pediatric case with acute myeloid leukemia: a case report and literature review - Wang, Liang; Qiu, Fangzhou; Shen, Yongming; Chen, Sen; Si, Ping (Frontiers in Oncology, 2023)
The lysine(K)-specific methyltransferase 2A gene (KMT2A), previously known as mixed lineage leukemia (MLL), frequently rearranged in acute leukemia, belongs to one of the most promiscuous genes and has been found fused to more than 80 different partners. KMT2A::SEPTIN6 fusion is a relatively uncommon rearrangement observed in pediatric acute myeloid leukemia (AML) patients, some of which may harbor other mutations. We herein report a case of AML-M4-infant with KMT2A::SEPTIN6 fusion and DIS3 variant. The 8-month-old girl presented with leukocytosis, anemia and thrombocytopenia. A bone marrow smear disclosed that 64% of the total nucleated cells were blasts. Karyotype analysis showed 46,X,t(X;11)(q24;q23)[10]/46,XX [10]. Fluorescence in situ hybridization analysis suggested a possible break in the KMT2A gene.After whole transcriptome sequencing, Exon 9 of KMT2A was fused in-frame with Exon 2 of SEPTIN6. This is a typical type of chromosomal rearrangement leading to the KMT2A::SEPTIN6 fusion. Meanwhile, DIS3 variant [c.2065C>T, p.R689X, variant allele frequency (VAF): 39.8%] was identified. KMT2A::SEPTIN6 fusion has been associated with the pathogenesis of AML, whereas DIS3 variants are relatively rare genetic events in pediatric AML. Regrettably, the relatives disagreed with the combination chemotherapy, and the patient eventually died of progressive disease. In conclusion, our findings provide a foundation for a better understanding of the genotypic profile of KMT2A::SEPTIN6 associated AML, and the co-existence of KMT2A::SEPTIN6 and DIS3 variant might contribute to the disease progression and transformation of AML.